2014
DOI: 10.4049/jimmunol.1401196
|View full text |Cite
|
Sign up to set email alerts
|

Selective Phosphorylation of the Dlg1AB Variant Is Critical for TCR-Induced p38 Activation and Induction of Proinflammatory Cytokines in CD8+ T Cells

Abstract: CD8+ T cells respond to TCR stimulation by producing proinflammatory cytokines, and destroying infected or malignant cells through the production and release of cytotoxic granules. Scaffold protein Discs large homolog 1 (Dlg1) specifies TCR-dependent functions by channeling proximal signals toward the activation of p38-dependent proinflammatory cytokine gene expression and/or p38-independent cytotoxic granule release. Two Dlg1 variants are expressed in CD8+ T cells via alternative splicing, Dlg1AB and Dlg1B, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…However, initial Dlg1 knockout studies have been unremarkable, possibly due to compensation of other Dlg family members or scaffolds during development [ 11 , 41 , 42 ]. Supporting this hypothesis, and validating our present and previous Dlg1 knockdown studies, we have recently demonstrated that acute in vitro dlg1 knockout in CD8+ T cells containing loxP sites flanking the dlg1 exon encoding a portion of PDZ1 and PDZ2 treated with Cre-recombinase were defective in p38 phosphorylation, induction of proinflammatory cytokine gene expression and CTL cytotoxicity [ 43 ]. Future studies utilizing acute Dlg1 knockout mice should allow for a more accurate assessment of the functional role of Dlg1 in T lymphocytes and other hematopoietic cell populations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, initial Dlg1 knockout studies have been unremarkable, possibly due to compensation of other Dlg family members or scaffolds during development [ 11 , 41 , 42 ]. Supporting this hypothesis, and validating our present and previous Dlg1 knockdown studies, we have recently demonstrated that acute in vitro dlg1 knockout in CD8+ T cells containing loxP sites flanking the dlg1 exon encoding a portion of PDZ1 and PDZ2 treated with Cre-recombinase were defective in p38 phosphorylation, induction of proinflammatory cytokine gene expression and CTL cytotoxicity [ 43 ]. Future studies utilizing acute Dlg1 knockout mice should allow for a more accurate assessment of the functional role of Dlg1 in T lymphocytes and other hematopoietic cell populations.…”
Section: Discussionsupporting
confidence: 86%
“…Another possibility is that Dlg1B-bound ZAP70 is activated by a non-Lck-dependent mechanism but is mal-positioned relative to p38, preventing optimal p38 phosphorylation. This lack in proper tyrosine kinase positioning may be caused by the spatial-dimensional absence of the i1A domain in Dlg1B, or the lack of Lck-dependent phosphorylation of Dlg1B on Y222, which has been proposed to serve as a conformational switch to open the Dlg1 scaffold to allow for the binding of additional ligands or proper juxtaposition of already bound ligands [ 43 ]. These findings do not exclude the possibility that Dlg1B allows for suboptimal and/or delayed p38 phosphorylation that is independent of Dlg1-associated Lck.…”
Section: Discussionmentioning
confidence: 99%
“…This specific modification renders DLG1 able to modulate p38 activation and the subsequent cytokine expression, highlighting the importance of this posttranslational modification as a key control for the DLG1 activities involved in lymphocyte biology. Moreover, blocking of DLG1AB phosphorylation was proposed as a novel therapeutic tool to specifically block proinflammatory cytokine production (Crocetti et al, 2014) DLG1 is able to interact with some tumour suppressors, such as Adenomatous polyposis coli and PTEN, and it was shown to regulate cell proliferation in many contexts. Hereafter, the regulation of DLG1 during the cell cycle should be important in order to strictly control cell growth.…”
Section: Post-translational Levelmentioning
confidence: 99%
“…Unlike the other four members of the NFAT family, which are regulated by calcium–calcineurin, NFAT5 is found in all cell types and is regulated by osmotic stress (Macian, ). DLG1 regulates Ag‐dependent cytoskeletal and signaling events by localizing to the junction between T cells and antigen‐presenting cells, also known as the immunological synapse (Crocetti, Silva, Humphries, Tibbs, & Miceli, ; Zanin‐Zhorov et al., ). Tumor necrosis factor receptor‐associated factor 3 (TRAF3) is an adaptor molecule that links upstream receptor signals to downstream gene activation in both adaptive immune cells and the innate immune system (Oganesyan et al., ; Yi, Lin, Stunz, & Bishop, ).…”
Section: Discussionmentioning
confidence: 99%